Audio Visual Dakwah Media Baru Khalid Basalamah Perspektif Honeycomb Social Media - Apang Abdul Goffar; Nanda Fahrun Nisa (LP2M UIN Sunan Kalijaga, 2021)
This article describes the audio-visual da'wah as a form of da'wah innovation in the digital era. By using the honeycomb social media concept, this paper will explore the role of the seven honeycomb social media frameworks in audio-visual da'wah activities on YouTube. This paper focuses on the discussion of the audio-visual da'wah conducted by Ustadz Khalid Basalamah on his personal YouTube channel. Khalid Basalamah Official Channel is one of the audio-visual da'wah activists through YouTube which has the most subscribers and its da'wah is in great demand by many people. By using the virtual observation method or online observation of audio-visual da'wah conducted by Ustadz Khalid Basalamah on his youtube channel. This article is important to read if you want to see the role of the honeycomb concept that has emerged in the last 10 years in the world of media studies and is widely used as a reference by social media researchers, in connection with Ustadz Khalid Basalamah's audio-visual da'wah activities on YouTube. Finally, it is known that there are two blocks in the honeycomb social media framework that have a role in seeing the success of Ustadz Khalid Basalamah's audio-visual da'wah.[Artikel ini menjelaskan tentang audio visual dakwah sebagai bentuk inovasi dakwah di era digital. Dengan menggunakan konsep honeycomb social media, tulisan ini akan mengeksplorasi peran tujuh kerangka honeycomb social media dalam aktivitas audio visual dakwah di youtube. Tulisan ini memfokuskan pembahasan pada audio visual dakwah yang dilakukan oleh Ustadz Khalid Basalamah di kanal youtube pribadinya. Kanal Khalid Basalamah Official merupakan salah satu aktivis audio visual dakwah melalui youtube yang memiliki pelanggan terbanyak dan dakwahnya sangat diminati oleh banyak kalangan. Dengan menggunakan metode pengamatan virtual atau pengamatan online atas dakwah audio visual yang dilakukan oleh Ustadz Khalid Basalamah di kanal youtubenya. Tulisan ini penting untuk dibaca jika ingin melihat peran konsep honeycomb yang muncul dalam 10 tahun terakhir di dunia media studies dan banyak dijadikan rujukan oleh para peneliti media sosial, dalam hubungannya dengan aktivitas audio visual dakwah Ustadz Khalid Basalamah di youtube. Akhirnya diketahui bahwa terdapat dua blok dalam kerangka honeycomb social media yang memiliki peran dalam melihat keberhasilan audio visual dakwah Ustadz Khalid Basalamah.]